Neptunium redox speciation at the illite surface. (1st March 2015) - Marsac, Rémi; Banik, Nidhu lal; Lützenkirchen, Johannes; Marquardt, Christian Michael; Dardenne, Kathy; Schild, Dieter; Rothe, Joerg; Diascorn, Alexandre; Kupcik, Tomas; Schäfer, Thorsten; Geckeis, Horst
Abstract: Neptunium (Np(V)) sorption onto a purified illite is investigated as a function of pH (3–10) and [Np V O2 + ]tot (3 × 10 −8 –3 × 10 − 4  M) in 0.1 M NaCl under Ar atmosphere. After about one week reaction time, only insignificant variation of Np sorption is observed and the establishment of reaction equilibrium can be assumed. Surprisingly, solid–liquid distribution ratios (Rd ) are clearly higher than those measured for Np(V) sorption onto illite under aerobic conditions. The observation that Rd increases with decreasing pe (pe = −log ae − ) suggests partial reduction to Np(IV), although measured redox potentials (pe values) at a first glance suggest the predominance of Np(V). Reduction to Np(IV) at the illite surface could indeed be confirmed by X-ray absorption near-edge spectroscopy (XANES). Np speciation in presence of the purified Na-illite under given conditions is consistently described by applying the 2 sites protolysis non-electrostatic surface complexation and cation exchange model. Measured pe data are taken to calculate Np redox state and surface complexation constants for Np(IV) are derived by applying a data fitting procedure. Constants are very consistent with results obtained by applying an existing linear free energy relationship (LFER). Taking Np(IV) surface complexation constants into account shifts the calculated Np(V)/Np(IV) redox borderline in presence of illite surfaces by 3–5 pe units (0.2–0.3 V) towards redox neutral conditions. Our study suggests that Np(V) reduction in presence of a sorbing mineral phase is thermodynamically favored.